DESKRIPTIVE STUDY OF TEACHER PERFORMANCE IN SMKN 4 LEBONG - Zulfianti Zulfianti; Johanes Sapri (DIADIK, 2019)
Teaching and learning activities in SMK 4 Lebong, can take place well supported by many factors, one of which is teacher work performance. In SMK 4 Lebong has 27 teachers who are often found teacher performance is not optimal in the teaching process, incompatibility of material taught with Learning Implementation Plans (RPP). Therefore teacher performance has a very important role for education.The aim of the study was to find out the causes of the performance of teachers in 4 Lebong Vocational High Schools were still low and to find out ways to improve teacher performance in SMK 4 Lebong. This study uses a descriptive method with a qualitative approach. Descriptive research method is a research method that describes the actual situation at the time of the research through collecting data which is then interpreted with prestige with each other so that the formulation and analysis of existing problems is obtained. Teacher performance in SMK 4 has been good, but the elements of quality are work, knowledge of work and initiatives that often causes teacher performance to be low. efforts made to improve teacher performance in SMK 4 Lebong based on SWOT analysis are one of them by improving performance based on quantity of work, improving performance based on improving the quality of work, improving performance with improved personal quality.